Activity-Based Restorative Therapy Promotes Progression from Asymmetry to Symmetry in Posture and Gait in a Child with Chronic, Incomplete Spinal Cord Injury - Laura Leon Machado; Kathryn Lucas; Andrea L. Behrman (MDPI AG, 2023)
Incomplete spinal cord injuries (ISCI) in pediatrics and adults can lead to asymmetric motor impairments exhibiting as asymmetries of posture and gait. Recently, rehabilitation guidelines for adults with neurologic injuries have focused on gaining a functional gait pattern as measured by speed and distance, even if asymmetry deficits persist. Activity-based restorative therapies (ABRT) take advantage of activity-dependent neuroplasticity to change an individual's neuromuscular capacity. This is a report of an ambulatory child with chronic ISCI presenting with significant postural and gait asymmetries who enrolled in an ABRT program. Across 79 ABRT sessions, the child gained symmetry during sitting, standing, and walking. Even though this child was a functional ambulator at enrollment, targeting symmetry of movements via improved neuromuscular capacity further enhanced her achievement of kinematically appropriate function for participation in daily activities.